Pengaruh Taxpayer Awareness dan Taxation Knowledge terhadap Taxpayer Compliance dalam Membayar Pajak Bumi dan Bangunan di Kecamatan Medan Satria Kota Bekasi - Nurrochman, Azzahra Syifa; Okabrian, Soni (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
The research is grounded in the concern over the low level of taxpayer compliance in paying property taxes, which can hinder the realization of optimal local revenue. To address this issue, this study investigates how the taxpayers' level of awareness and knowledge about taxation affect their compliance behavior. This study aims to examine the influence of taxpayer awareness and taxation knowledge on taxpayer compliance regarding property tax payments in the Medan Satria District. The study adopts a quantitative approach, specifically utilizing an associative method to explore the relationship between taxpayer awareness, taxation knowledge, and taxpayer compliance. The population of the study consists of 1,743 Property Taxpayers in Medan Satria District, with a minimum sample size of 399 respondents determined using Slovin's formula with a 5% margin of error. Data collection was conducted through a structured questionnaire using a Likert scale to assess the three variables. Prior to distribution, the questionnaire was tested for validity and reliability to ensure accurate and consistent measurement. Valid and reliable responses were then subjected to classical assumption tests to meet the requirements of the Best Linear Unbiased Estimator (BLUE). The data analysis involved descriptive statistics, partial and simultaneous hypothesis testing, and multiple linear regression to determine the effect of taxpayer awareness and taxation knowledge on taxpayer compliance. The results revealed that both variables have a significant and positive impact on taxpayer compliance.